Premorbid risk factors and acute injury characteristics of sport-related concussion across the national collegiate athletic association: findings from the concussion assessment, research, and education (CARE) consortium - Memmini, A. K.; Mosesso, K. M.; Perkins, S. M.; Brett, B. L.; Pasquina, P. F.; McAllister, T. W.; McCrea, M. A.; Broglio, S. P. (Sports Medicine, 2023)
Background: Previous sport-related concussion research highlights post-injury characteristics that influence recovery trajectories; however, there is limited information regarding premorbid factors that affect sport-related concussion risk. Objective: We aimed to (a) compare premorbid demographic factors among a large cohort of collegiate student athletes who did or did not sustain a sport-related concussion and (b) assess differences in acute injury characteristics based on biological sex and contact level. Methods: We conducted a cohort study of university student athletes from 22 sports enrolled in the Concussion Assessment, Research, and Education (CARE) Consortium study from 2014 to 2021 (n = 1804 student athletes with sport-related concussions; n = 21,702 student athletes without sport-related concussions). Results: Statistical analyses indicated student athletes who self-identified as Black (odds ratio [OR] = 1.61; 95% confidence interval [CI] = 1.42, 1.81) or multiracial (OR = 1.32; 95% CI 1.10, 1.59) demonstrated greater odds of experiencing sport-related concussions than White-identifying student athletes. Additional findings suggest male athletes (OR = 1.47; 95% CI 1.20, 1.81) and contact sport student athletes (OR = 1.40; 95% CI 1.16, 1.70) may be at increased odds for sport-related concussions if they were previously diagnosed with attention deficit hyperactive disorder. Notable post-injury characteristics across sexes included differences in the incident loss of consciousness (male: 5.9%, female: 2.6%; p < 0.001), post-traumatic amnesia (male: 13.6%, female: 5.1%; p < 0.001), and retrograde amnesia (male: 6.8%, female: 2.8%; p < 0.001). A greater proportion of contact-sport student athletes experienced an altered mental status (52.7%) than limited contact (36.2%) and non-contact (48.6%) [p < 0.001]. Last, student athletes participating at lower contact levels were more likely to have a longer delay in removal from activity following injury (contact: 73.6 ± 322.2 min; limited contact: 139.1 ± 560.0 min; non-contact: 461.4 ± 1870.8 min; p = 0.005). Conclusions: The present study provides contemporary pre- and post-sport-related concussion injury characteristics using a considerably sized cohort of collegiate student athletes. These findings support previous work suggesting sport-related concussion results in complex individualized clinical presentations, which may influence management strategies.